2020
DOI: 10.1038/s41525-020-00155-8
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of genetic diseases as a cause of mortality in infants receiving whole genome sequencing

Abstract: Understanding causes of infant mortality shapes public health policy and prioritizes diseases for investments in surveillance, intervention and medical research. Rapid genomic sequencing has created a novel opportunity to decrease infant mortality associated with treatable genetic diseases. Herein, we sought to measure the contribution of genetic diseases to mortality among infants by secondary analysis of babies enrolled in two clinical studies and a systematic literature review. Among 312 infants who had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 75 publications
0
42
0
Order By: Relevance
“…Precision medicine utilizing rapid whole genome sequencing (rWGS) can substantially decrease morbidity and mortality among critically ill infants by informing changes in management based on molecular diagnoses. 1,2 Evidence about the diagnostic yield rate and clinical utility of rWGS in critical care settings, including Neonatal Intensive Care Units (NICUs) and Pediatric Intensive Care and Pediatric Cardiovascular Intensive Care Units (PICUs and PCICUs) is robust and growing. [1][2][3][4][5][6][7][8][9][10][11] Requiring a suspicion of a genetic disorder will miss half of all genetic conditions leading to NICU or PICU admission and delays in ordering testing.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Precision medicine utilizing rapid whole genome sequencing (rWGS) can substantially decrease morbidity and mortality among critically ill infants by informing changes in management based on molecular diagnoses. 1,2 Evidence about the diagnostic yield rate and clinical utility of rWGS in critical care settings, including Neonatal Intensive Care Units (NICUs) and Pediatric Intensive Care and Pediatric Cardiovascular Intensive Care Units (PICUs and PCICUs) is robust and growing. [1][2][3][4][5][6][7][8][9][10][11] Requiring a suspicion of a genetic disorder will miss half of all genetic conditions leading to NICU or PICU admission and delays in ordering testing.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…1,2 Evidence about the diagnostic yield rate and clinical utility of rWGS in critical care settings, including Neonatal Intensive Care Units (NICUs) and Pediatric Intensive Care and Pediatric Cardiovascular Intensive Care Units (PICUs and PCICUs) is robust and growing. [1][2][3][4][5][6][7][8][9][10][11] Requiring a suspicion of a genetic disorder will miss half of all genetic conditions leading to NICU or PICU admission and delays in ordering testing. [6][7] With rWGS, results are returned to the clinical team treating critically ill infants and children within a median time of 2 days, thereby shortening the time from diagnostic inquiry to more effective treatment or redirection of care.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Studies have estimated that genetic diseases are present in approximately 16% of neonates in regional ICUs; furthermore, there is high mortality in infants with genetic diseases, which accounts for an estimated 20% of deaths in this age group, and in one center, accounted for an estimated 45% of neonatal intensive care unit (NICU) deaths over a ten-year period [ 25 , 26 ]. It is proposed that the primary benefits of early genetic diagnosis in these patients include both the rapid implementation of targeted interventions that may decrease morbidity, as well as the rapid identification of likely futile intensive care in the course of what may otherwise be a protracted diagnostic approach during, which parents may experience “inappropriate hope” or “needless guilt.” Meanwhile, secondary benefits may include guiding parents regarding the risk of recurrence in future children as well as possible overall healthcare cost reductions [ 1 , 27 ].…”
Section: Next-generation Sequencing For Diagnostic Evaluation Of Critically Ill Newbornsmentioning
confidence: 99%
“…An early precise diagnosis could improve the surviving rate and reduce the admission rate in the PICU. A recent study revealed that the mortality in infants with genetic diseases was 21.6% (205 of 948 infant deaths)(Kingsmore et al, 2020) Jacob et al (2015). found that only 5% of 641 deceased NICU patients had genetic defects.…”
mentioning
confidence: 99%